Lawsone derived Zn(ii) and Fe(iii) metal organic frameworks with pH dependent emission for controlled drug delivery. (28th July 2021) - Sirajunnisa, P.; George, Liz Hannah; Manoj, N.; Prathapan, S.; Sailaja, G. S.
Abstract : Fluorescent biocompatible porous carriers have been investigated as suitable probes for drug delivery and sensing applications owing to their intrinsic fluorescence and high surface area originating from their porous structure complemented with tunable pore size/surface properties. Abstract : Fluorescent biocompatible porous carriers have been investigated as suitable probes for drug delivery and sensing applications owing to their intrinsic fluorescence and high surface area originating from their porous structure complemented with tunable pore size/surface properties. Here, we present a facile synthesis of biocompatible Zn(ii ) and Fe(iii ) fluorescent metal organic frameworks (MOFs) derived from 2-hydroxy-1, 4-naphthoquinone (lawsone), a naturally occurring naphthoquinone, for controlled drug delivery applications with pH dependent emission behavior. X-ray diffraction patterns demonstrated an intense peak at a 2-theta value of 7°, indicative of MOF formation, which is further corroborated by a continuous mesoporous network structure observed in HRTEM analysis. The N2 adsorption–desorption isotherms (BET) confirmed the mesoporous structure with a pore size of 9 to 11 nm with a typical type IV isotherm. UV-visible and fluorescence measurements indicated red shift with intense broad emission at 670 nm together with a change in the emission intensity in response to pH. FTIR analysis confirmed the metal (Zn and Fe) coordination of lawsone. The onset degradation temperatures of ZnMOF and FeMOF are 220 °C and 170 °C, respectively, confirming their thermal stability. Drug (Ibuprofen) release studies demonstrated a maximum loading of 43.19% for FeLw 60 among the Zn/Fe MOF series with a controlled release of 14.5% at 96 h. The results demonstrate that both loading and release profiles are governed by the pore size and pore volume factors of the MOFs. The MTT assay validates the cytocompatibility of the new class of colorimetric and fluorescent MOFs from lawsone and hence they could be proposed for controlled release applications.